Объяснение:
1. a₁=-2 a₁₀=16 a₁₂=?
a₁₀=a₁+(10-1)*d=16
-2+9*d=16
9*d=18 |÷9
d=2 ⇒
a₁₂=a₁+(12-1)*d=-2+11*2=-2+22=20
ответ: а₁₂=20.
2. a₇=43 a₁₅=3 a₁₂=?
{a₇=a₁+6d=43
{a₁₅=a₁+14d=3
Вычитаем из нижнего уравнения верхнее:
8d=-40 |÷8
d=-5 ⇒
a₁+6*(-5)=43
a₁-30=43
a₁=73
a₁₂=73+11*(-5)=73-55=18
ответ: a₁₂=18.
3. a₁=30 d=-0,4 a₁₂=?
a₁₂=30+11*(-0,4)=30-4,4=25,6
ответ: a₁₂=25,6.
4. a₁₀=9,5 S₁₀=50 a₁₂=?
Sn=(a₁+an)*n/2
(a₁+9,5)*10/2=50
(a₁+9,5)*5=50 |÷5
a₁+9,5=10
a₁=0,5
a₁₀=a₁+9d=9,5
0,5+9d=9,5
9d=9 |÷9
d=1 ⇒
a₁₂=a₁+11d=0,5+11*1=0,5+11=11,5.
ответ: а₁₂=11,5.
Используем формулу квадрата разности a²-2ab+b² = (a-b)²
29.
4+49x²-28x = 49x²-28x+4 = (7x)²- 2·7x·2 + 2² = (7x-2)² = (7x-2)(7x-2)
32.
-20yx+25y²+4x² = 25y²-20yx +4x² = (5y)²- 2·5y·2x + (2x)² = (5y-2x)² =
= (5y-2x)(5y-2x)
35.
25+9y²-30y = 9y²-30y+25 = (3y)²- 2·3y·5 + 5² = (3y-5)² = (3y-5)(3y-5)